Clinical Pharmacology Aspects of Some Tocolytic Drugs Used in Pregnant Women at Risk of Preterm Birth - E. A. Sоkоvа; R. A. Chilova; O. A. Demidova; K. O. Akopov (Регуляторные исследования и экспертиза лекарственных средств)
Spontaneous preterm birth is one of the most pressing issues in obstetrics, as it remains one of the leading causes of newborn morbidity and mortality. Pending issues of aetiology, pathogenesis, and absence of medicinal products indicated for the treatment of spontaneous preterm labour pose a challenge for rational pharmacotherapy. The paper presents the results of a scientific literature review on the problem of rational pharmacotherapy of spontaneous preterm labour using tocolytic drugs — calcium channel blockers, cyclooxygenase inhibitors. The paper summarises specific pharmacokinetic parameters of these drugs during pregnancy. It discusses pharmacogenetic aspects of using tocolytic drugs in pregnant women and their potential clinical effects. It was demonstrated that women with threatened miscarriage had high interindividual variability in nifedipine plasma concentrations depending on CYP3A5 genotype. It was shown that certain genetic polymorphisms of CYP2C9 may lead to an increased metabolic rate and an increase in indomethacin clearance resulting in the reduction of its efficacy. Yet, there is minimal research regarding this issue. Therefore, further research is needed to assess the impact of CYP3A5 and CYP2C9 genotypes on the efficacy and safety of nifedipine and indomethacin used as tocolytic drugs in obstetrics.